Collision Avoidance of UAV Formation Using Geometric Approach and Relative Velocity Vector in Three-dimensional Space 기하적 방법 및 상대 속도 벡터를 이용한 3차원 상의 UAV 편대 충돌 회피 기법 - Jung, Jiwon; Park, Jongho; Lim, Jaesung (Journal of the Korean Society for Aeronautical and Space Sciences, 2024)
In this study, a three-dimensional collision avoidance algorithm which uses relative velocity vectors and line-of-sight vectors based on geometric approach is proposed. After detecting collision condition of an obstacle by Closest Point of Approach (CPA), an avoidance maneuver is calculated by rotating the relative velocity vector using Rodrigues rotation formula. This avoidance maneuver considers efficiency in terms of angle change. Based on the proposed algorithm, collision avoidance framework for Unmanned Aerial Vehicle (UAV) formation flight is presented. When a UAV formation detects an obstacle, each UAV uses the proposed avoidance algorithm. To avoid collision against each other in the formation, obstacle's collision radius is varied for each UAV. Numerical simulations are performed to validate the proposed collision avoidance algorithm and UAV formation flight.
Keywords: Collision Avoidance; Formation Flight; Relative Velocity Vector; Unmanned Aerial Vehicle